Updated Spectrophotometric Investigation of Copper Complexes with Thiomicher’s Ketone and Bromopyrogallol Red - Gao, Hong-Wen; Zi, Yan-Qin; Gu, Jia-Shan; Ye, Su-Mei (Asian Journal of Chemistry, 2010)
The novel investigation of the copper complexes with thiomicher's ketone (TMK) and bromopyrogallol red (BPR) was carried out at pH 7 by spectral correction technique. The characteristic factors were calculated, for example, complex ratio and stability constant. The results have shown that the Cu(TMK)2 and Cu(BPR)2 were formed and their real stepwise molar absorptivities were determined simply at pH 7. Their cumulative stability constants are 5.08 x 1011 and 5.02 x 1011 respectively.